2002
DOI: 10.1161/01.hyp.0000037217.96002.8e
|View full text |Cite
|
Sign up to set email alerts
|

Results of the D iet, E xercise, and W eight Loss I ntervention T rial (DEW-IT)

Abstract: Abstract-National guidelines for the prevention and treatment of hypertension recommend sodium reduction, weight loss, the Dietary Approach to Stop Hypertension (DASH) diet, and regular aerobic exercise. However, no trial has assessed the efficacy of simultaneously implementing all of these recommendations. The objective of this study was to determine the effects on blood pressure and other cardiovascular disease risk factors of a comprehensive lifestyle intervention. We conducted a randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
1
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(194 citation statements)
references
References 17 publications
4
177
1
12
Order By: Relevance
“…The extent to which the risk factors, when present, were modified in our cohort was comparable to the intervention groups in previously published studies. Thus, there was sustainable weight loss in those who were overweight,36, 37 lowering of blood pressure in those with high levels,38 improvement of the lipid profile and insulin resistance in those with baseline abnormalities,33, 39 and promotion of a healthy diet and exercise habits,33, 40, 41 findings similar to observations in high‐risk populations 42, 43. Importantly, no perceptible decline among those with relatively normal values was observed, indicating that health was maintained in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the risk factors, when present, were modified in our cohort was comparable to the intervention groups in previously published studies. Thus, there was sustainable weight loss in those who were overweight,36, 37 lowering of blood pressure in those with high levels,38 improvement of the lipid profile and insulin resistance in those with baseline abnormalities,33, 39 and promotion of a healthy diet and exercise habits,33, 40, 41 findings similar to observations in high‐risk populations 42, 43. Importantly, no perceptible decline among those with relatively normal values was observed, indicating that health was maintained in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10 Weight loss associated with lifestyle modifications such as diet and regular exercise are important and remain the first-line treatment for obesity and obesity-related hypertension. [11][12][13][14][15] Whelton et al 16 reported in a meta-analysis of 54 randomized, controlled trials comprising 2419 participants that aerobic exercise was associated with a significant reduction in mean systolic and diastolic blood pressure (BP) in both overweight and normal-weight participants regardless of whether they were hypertensive or normotensive on admission to the investigation. A number of studies, including a series of the Dietary Approaches to Stop Hypertension (DASH) diet studies, [17][18][19] showed that not only the dietary pattern, but also aerobic exercise and calorie restriction were necessary for weight loss, weight loss-induced BP reduction and improvement of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss with life-style modifications can result in significantly better BP control among hypertensive patients with pharmacological treatments. 15,20 Although both life-style modifications (that is, calorie-restricted diet and exercise) are recommended for weight loss, it has not been fully clarified which is more effective with regards to weight loss-induced BP reduction in obese hypertensive patients. Therefore, in the present study, we sought to clarify the differences in neurohormonal mechanisms in weight loss-induced BP reduction between mild caloric restrictive diet and exercise over a 24-week period.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, sixteen randomized controlled trails "RCTs" were identified that fulfilled the criteria described above, three of which were identical and therefore eliminated. Thus the meta-analysis includes a total of thirteen studies [27][28][29][30][31][32][33][34][35][36][37][38][39] (Fig. 1). …”
Section: Methodsmentioning
confidence: 99%